USING ARTIFICIAL INTELLIGENCE TO ENHANCE THE QUALITY OF PHOTOGRAPHIC IMAGES: ETHICAL AND AESTHETIC ASPECTS (American Journal of Technology and Applied Sciences, 2025)
Modern artificial intelligence (AI) technologies have radically changed approaches to processing and enhancing photographic images. Along with increasing technical capabilities, ethical and aesthetic issues related to the veracity of visual information, authorship, and the perception of artistic images are becoming increasingly important. This article analyzes the main applications of AI in photographic enhancement and discusses their implications for artistic practice and the public perception of visual content.